Comparative study of adverse effect profile of first line drugs Zidovudine (ZDV) + Lamivudine (3TC) + Nevirapine (NVP) Vs Tenofovir (TDF) + Lamivudine (3TC) + Atazanavir (ATV) + Ritonovir (RTV) in HIV/AIDS patients - Desai, Savithri; Kurli, Sankar; G., Harinika (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The biggest threat to mankind from the health perspective is probably the virus Human Immunodeficiency Virus (HIV) responsible for a serious disease known as Acquired Immune Deficiency Syndrome (AIDS). To compare the adverse effect profile of two antiretroviral regimens i.e, Zidovudine (ZDV) + Lamivudine (3TC) + Nevirapine (NVP) [regimen A] Vs Tenofovir (TDF) + Lamivudine (3TC) + Atazanavir(ATV) + Ritonavir (RTV) [regimen B] by clinical and biochemical methods. Methods: This prospective, observational study was carried out in 200 HIV positive patients receiving first line and second-line antiretroviral therapy (ART) at ART centre, GGH, Vijayawada. Out of 200 patients, 100 patients received regimen A [(ZDV) + (3TC) + (NVP)] and 100 patients were treated with regimen B [(TDF) + (3TC) + (ATV) + (RTV)]. The collected data has been analysed and presented. Results: Out of 200 patients, 110 patients developed ADRs. In this 110, 38 patients received regimen A and 18 patients received regimen B and had CD4 + count <250 cells/mm3. In the remaining 54 patients, 20 patients received regimen A and 34 patients received regimen B who had CD4+ count >250 cells/ mm3. Conclusions: The ADRs were most common in those patients whose CD4+ count is less than 250cells/cu mm. Though the patients on second line showed significant increase in CD4+count, number of patients with ADRs were also more with regimen B. Though atazanavir containing regimen is more efficacious than zidovudine containing regimen, but regimen B produces more serious adverse effects. So, second line drugs are reserved for treatment failures to first line, drug resistance and for those not tolerating first line drugs.